2004
DOI: 10.4049/jimmunol.173.9.5415
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Expression of CTLA-4 Controls Lymphoproliferation in IL-2-Deficient Mice

Abstract: IL-2-deficient mice develop a lymphoproliferative and autoimmune disease characterized by autoimmune hemolytic anemia (AHA) and inflammatory bowel disease. We have previously reported that IL-2 is necessary for optimal up-regulation of CTLA-4, an inducible negative regulator of T cell activation. In this study, we have tested the hypothesis that reduced expression of CTLA-4 in IL-2-deficient T cells contributes to the pathogenesis of disease in IL-2-deficient mice. Expression of CTLA-4 as a transgene completel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 43 publications
(46 reference statements)
1
17
0
Order By: Relevance
“…A recent study has addressed the role of CTLA-4 expression in the development of autoimmune disease in IL-2 Ϫ/Ϫ mice (50). In this study CTLA-4 transgenic overexpression was shown to partially rescue the lymphoproliferative disorder seen in IL-2 Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 74%
“…A recent study has addressed the role of CTLA-4 expression in the development of autoimmune disease in IL-2 Ϫ/Ϫ mice (50). In this study CTLA-4 transgenic overexpression was shown to partially rescue the lymphoproliferative disorder seen in IL-2 Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 74%
“…For example, when Ag was expressed as an "endogenous" tissue Ag in islets (a setting more relevant to transplantation), an intact CTLA-4 locus prevented diabetes by reducing the accumulation of "autoreactive" TCR-transgenic CD4 cells, but did not induce anergy in terms of proliferative response ex vivo (43). Transgenic overexpression of CTLA-4 appears to inhibit autoimmunity in IL-2-deficient mice by limiting effector cell responsiveness (44). Similarly, transplantation in the face of CTLA-4 blockade suggests that CTLA-4 normally limits activation of alloreactive CD4 and CD8 cells, thereby decreasing their frequency and differentiation (12).…”
Section: Discussionmentioning
confidence: 99%
“…(30.4) and when, in a separate susceptibility gene combination, the resistance allele in mouse Ctla4 can completely mask the potent disease-causing effect of a particular susceptibility allele at another locus. It has also been shown that a third locus, insulin dependent diabetes susceptibility 3 (Idd3), which is believed to be the interleukin-2 gene [32,33] can influence the production of CTLA-4 [30,34]. We, therefore, propose that AITD, type 1 diabetes and cooccurring type 1 diabetes and AITD manifest due to different, but overlapping combinations of susceptibility and resistance alleles of multiple loci, and that in isolated type 1 diabetes (up to 90% of cases) the constellations of alleles giving rise to this disease mask the allelically variable effect of CTLA4 to a much greater degree than the combination of alleles causing AITD or type 1 diabetes + TPOAbs as studied here.…”
Section: Discussionmentioning
confidence: 99%